Signal to Interference Plus Noise Ratio Analysis of Femtocells in Advanced Long-Term Evolution (LTE) - Hurissa, Dejene (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2021)
This work aims to investigate signal to interference plus noise ratio of femtocells for indoor users under long term evolution (LTE). Ethiopia has different cities with big buildings, companies, hotels, hospitals, condos, residential houses, and others. Signal attenuators like several walls, number of floors, and others affect the quality of the signal. For this reason, femtocells are taken as a solution to enhance the signal quality. This work considers signal to interference plus noise ratio with the system flow chart. The performance analysis used MultiWall Multi Floor (MWMF), an indoor propagation model. Path losses and signal to interference plus noise ratio are used to measure the performance in this work. The outcome of this work shows that femtocells are capable of enhancing signal quality for indoor users.